JFAS 2020
DOI: 10.51128/jfas.2020.a020
|View full text |Cite
|
Sign up to set email alerts
|

Histology, lectin histochemistry and ultrastructure of interdigital gland in crossbred sheep

Abstract: Histology, lectin histochemistry and ultrastructure of interdigital gland in sheep was studied using six adult cross bred sheep of either sex collected from the Meat Technology Unit, College of Veterinary and Animal Sciences, Mannuthy. The manus and pes were detached from the rest of limbs and after recording the gross observations, the interdigital glands were fixed in 10 per cent neutral buffered formalin and processed for histological examinations. Stratified squamous epithelium with a prominent keratin lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
3
1
0
Order By: Relevance
“…The skin thickness, which was a significant covariate in the PMHS injury risk functions, was largely homogeneous across the ovine body regions, showing insignificance as a covariate in the ovine risk functions [6]. The skin thickness measurements extracted from ultrasound in this study were in agreement with values previously found in the ovine population from other sources [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…The skin thickness, which was a significant covariate in the PMHS injury risk functions, was largely homogeneous across the ovine body regions, showing insignificance as a covariate in the ovine risk functions [6]. The skin thickness measurements extracted from ultrasound in this study were in agreement with values previously found in the ovine population from other sources [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that the interdigital gland in ovine animals has a sweat gland component with dual secretory activity (Pourlis, 2010 ). In our study, following many studies (Abdi et al., 2020 ; Maya et al., 2020 ), a small number of hair follicles in the dermis close to the epidermis, sebaceous gland structures around the hair follicles and a large number of apocrine glands in the area close to the connective tissue capsules were observed. Contrary to Janicki et al.…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that the interdigital gland in ovine animals has a sweat gland component with dual secretory activity (Pourlis, 2010). In our study, following many studies (Abdi et al, 2020;Maya et al, 2020), a small number of hair follicles in the dermis close to the epidermis, sebaceous gland structures around the hair follicles and a large number of apocrine glands in the area close to the connective tissue capsules were observed. Contrary to Janicki et al (2003), who reported that the interdigital gland of roe deer (Capreolus capreolus L.) was devoid of connective tissue capsule and sweat glands, the connective tissue capsules layer in our study consisted of a few fibrocytes and fibroblast layers, dense collagen fibres, adipose tissue and blood vessels.…”
Section: Measurement Parameterssupporting
confidence: 78%
See 1 more Smart Citation